The Factors Affecting Turnover Intention With The Moderating Role Of Intrinsic Intention In Jordanian Five-Star Hotels - Rashidah, Mohamad Ibrahim; Jarwan Ayman, Mousa Ali (2018)
In majority of industries, the issue of high rates of turnover has always exists as a result of which several studies have been dedicated to it, particularly in the hospitality industry context. This study examined the moderating effect of intrinsic motivation on the relationship be-tween factors affecting turnover intention namely, HRMs and work engagement in Jordanian five-star hotels. The study provided details of the findings in every theme highlighted and described the relationships between the factors, using one single model. This study also conducted a comprehensive review of literature and presented quantitative findings on turnover intention from Jordan. Based on the find-ings, there is a positive and significant relationship between HRMs and work engagement, and turnover intention, with the moderating role of intrinsic motivation. The study has implications to theory in that it provided an expansive explanation of the outcomes of HRMs and work engagement in five-star hotels and their connection to the employees’ turnover intentions.